Trend assessment of changing climate patterns over the major agro-climatic zones of Sindh and Punjab - Qureshi, Haris Uddin; Shah, Syed Muzzamil Hussain; Teo, Fang Yenn (Frontiers in Water, 2023)
Pakistan is an agrarian economy with 30 % of its land area under cultivation, and 93% of its water resources are utilized for the agricultural production. Therefore, the changing climate patterns may adversely affect the agriculture and water resources of country. This study was conducted to assess the climate variations over the major agro-climatic zones of Sindh and Punjab, that serve as an important hub for the production of major food and cash crops in Pakistan. For this purpose, the climate data of 21 stations was analyzed using the Mann-Kendall test and Sen's slope estimator method for the period 1990-2022. The results obtained from the analysis revealed that in Sindh, the mean annual temperature rose by about 0.1 to 1.4 °C, with about 0.1 to 1.2 °C in Cotton-Wheat Sindh, and 0.8 to 1.4 °C in Rice-Other Sindh during the study period. Similarly, in Punjab, the mean annual temperature increased by about 0.1 to 1.0 °C, with 0.6 to 0.9 °C in Cotton-Wheat Punjab, and 0.2 to 0.6 °C in Rainfed Punjab. Seasonally, warming was found to be highest during the spring season. The precipitation analysis showed a rising annual precipitation trend in Sindh (+30 to +60 mm) and Punjab (+100 to 300 mm), while the monsoon precipitation increased by about 50 to 200 mm. For winter precipitation, an upward trend was found in Mixed Punjab, while the remaining stations showed a declining pattern. Conclusively, the warming temperatures as found in the analysis may result in increased irrigation requirements, soil moisture desiccation, and wilting of crops, ultimately leading to low crop yield and threatening the livelihoods of local farmers. On the other hand, the increasing precipitation may favor the national agriculture in terms of less freshwater withdrawals. However, it may also result in increased rainfall-induced floods inundating the crop fields, and causing water logging and soil salinization. The study outcomes comprehensively highlighted the prevailing climate trends over the important agro-climatic zones of Pakistan, that may aid to devise an effective climate change adaptation and mitigation strategy to ensure the state of water and food security in the country.